Assessment of Irrigation System Performance and Its Associated Impacts on Poverty - Murtiningrum Murtiningrum; Sigit Supadmo Arif (agriTECH, 2005)
It is indicated that the level of performance of an irrigation systefrz affects the benefit received by farmers. Low level of performance leads on the low farmers' income, which furthermore affects farmers' welfare. On the opposite, farmers with low level of welfare have limited capability to manage their irrigation system so the level of performance of the system declines. This created a vicious circle of low performance and poverty. This paper aims to assess irrigation system peformance, relate the performance with poverty in the system, and examine possibilites of poverty alleviation through improvement of irrigation system performance. Irrigation performance assessment comprises of characterization of irrigation system and performance assessment by using indicators. The study has been conducted in four irrigated systems in Java, namely Klambu Kiri, Glapan, Kalibawang, and Krogowanan. Lesson learnt were drawn from cases of the selected systems to find out factors affecting irrigation performance and how irrigation system performance affects farmers' welfare. Possible efforts to improve irrigation system performance to alleviate poverty are crop diversification, Irrigation Management Transfer, empowerment of Water Users' Association (WUA), locally specific farming, and off farm job opportunity. To implement those efforts there are some constraints to deal with, such as limited technical capability of farmers, diversity of social and culture, and limited available data and information.